Prediksi Penjualan Motor Honda pada Dinamika Motor Kupang menggunakan Autoregressive (AR) - Theresia Felisitas Dena; Franki Yusuf Bisilisin (Lembaga Pengembangan Kinerja Dosen, 2025)
The motorcycle industry in Indonesia is experiencing rapid growth, marked by the increasing number of two-wheeled vehicles every year. Dealer Dinamika Motor Kupang, also known as PT. Dinamika Sejahtera Motor, is one of the authorized Honda motorcycle dealers in Kupang, East Nusa Tenggara. Dinamika Motor Kupang faces the challenge of predicting market demand in order to design a more effective business strategy. Based on the number of motorcycle sales from 2022-2024, there are increases and decreases in the number of motorcycle sales. Therefore, a system is needed to predict motorcycle sales so that it can determine the sales level in the following months and years. This study aims to make a prediction of Honda motorcycle sales using the Autoregressive (AR) method. This method was chosen because it is able to analyze historical data patterns and provide accurate sales estimates. This study uses Honda motorcycle sales data for the period 2022–2024. Based on the test results, the MAPE value obtained was 22.73% with the normal distribution AR model, and 7.81% with the binomial distribution AR model. These results indicate that the binomial distribution AR model is more optimal in predicting motor sales on Beetle Motor Dynamics.